In hot water: The impact of burn injuries from hot water bottles — Experience of a UK burns unit and review of the literature. Issue 4 (June 2019) - Begum, Fahima; Khajuria, Ankur; Abdi, Hodan; Williams, Andrew; Jones, Isabel; Leon-Villapalos, Jorge; Collins, Declan; Atkins, Joanne
Highlights: Over 14 months, 80 patients were managed for hot water bottle (HWB) burns. In this period, 37 surgical procedures were received for this cohort of patients. It has cost our trust over £68, 6340 to manage such burns during this period. HWB burns can be associated with significant morbidity and complications. Abstract: Introduction: Hot water bottles (HWBs) are a common domestic item in the UK. Their use is associated with burns injuries, either by contact for prolonged periods with the skin, or through the HWB leaking or bursting. Methods: We used electronic health records to retrospectively review HWB related burns treated by the Burns Service at Chelsea and Westminster Hospital between January 2017–March 2018. We analysed the mechanism of injury, size and depth of burn, method of treatment and costs associated with HWB burns in our centre. Results: 80 patients sustained HWB burns during this period, with a similar incidence of contact burns (41/80, 51.3%) and scalds (38/80, 47.5%), with one steam burn. The commonest area burnt was the lower limb (40/80, 50%). Most burns had a TBSA of 1% or smaller (50/80, 62.5%). 30 patients had full thickness burns, with 37 in total received operative management. We estimate that the total cost for managing this cohort of patients was over £68, 634. Conclusions: There are a significant proportion of patients presenting with HWB burns that could be prevented, with significant impact on patient morbidity and resource burden on the NHS. Targeted public awareness campaigns are needed to ameliorate these injuries.